Sri Lanka : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
The macroeconomic stability of Sri Lanka is analyzed. Reflecting high domestic inflation relative to trading partners, the real effective exchange rate appreciated by 2 percent. Infrastructure development is a central element of the government's medium-term development strategy. Further efforts to reduce quasi-fiscal losses of the energy companies through adjustments in electricity tariffs, combined with balance sheet restructuring and enhanced operational efficiency are encouraged. Improvement over the quality and coverage of fiscal statistics and the remaining issues needed to meet the Special Data Dissemination Standard (SDDS) requirements are encouraged.